Performance of a 160 cc Four-Stroke Engine Using Non-Programmable Aftermarket CDI and Aftermarket Ignition Coil When Operating With Three Types of Gasoline - Nurcahyadi, Teddy; Wahyudi, Wahyudi; Ruswanto, Dwi Isnaini; Ramadhani, Fithrio Manggala; Sidiq, Burhannudin; Handoko, Wahyu Tri (Semesta Teknika, 2017)
Ignition timing and output voltage must be re-tuned when the engine used different types of fuel.Â This research aimed to investigate the effectiveness of CDI and ignition coil upgrade, both separately and combined, when various types of fuel was used by the engine.Â This research was done on a 160 cc four-stroke engine of a Honda motorcycle with compression ratio 9:1.Â The types of fuel used by the engine in this research was RON 88, RON 90, and RON 95 gasoline fuels. The engineâs torque was measured on an inertial type motorcycle chassis dynamometer.Â The fuel consumption data was obtained by on road test, the value of the data was calculated by dividing the distance being traveled with the volume of fuel being consumed. The result of this research showed that when RON 88 gasoline was used, the influence of aftermarket CDI and aftermarket ignition coil gave almost comparable impacts to the increase of torque.Â The combination of aftermarket CDI and aftermarket ignition coil was found to influence the largest torque increase percentage of 5.3% when RON 90 gasoline was used.Â When RON 95 gasoline was used, the aftermarket ignition coil influenced the largest torque increase percentage of 4.3% at lower engine speed and 7.4% at higher engine speed.Â The aftermarket CDI and aftermarket ignition coil, whether used separately or combined, always gave worse impact to fuel consumption when RON 88 and RON 90 gasoline was used. The opposite is true when RON 95 was used.